Optimization of jackfruit seed starch-soya protein isolate ratio and process variables for flaxseed oil encapsulation - BHUSHAN, BIBWE; MANI, INDRA; KAR, ABHIJIT; DATTA, ANIRBAN (The Indian Journal of Agricultural Sciences, 2017)
The attribution as functional food ingredient of omega-3 fatty acid encouraged food researchers and industry for development of foods enriched with omega-3 fatty acids. Flaxseed oil (FSO) is the prolific vegetarian source of alpha linolenic acid (Ï‰-3) for food enrichment, but its direct incorporation in food is problematic due to its high oxidation susceptibility. Microencapsulation of FSO using spray drying with jack fruit seed starch (JSS)-soya protein isolate (SPI) coating combination was studied as it is widely used approach to address the issue. The study was aimed at optimization of JSS-SPI ratio and process variables for microencapsulation of FSO with goals of maximization of encapsulation efficiency (EE), minimization of peroxide value (PV) and desired range of moisture content (MC:3-5, % wb) using Response surface methodology (RSM). The Box Behnken design (3k) was used to plan the experiments with three independent variables, viz. JSS-SPI ratio (1:1, 3:1 and 5:1), oil loading (20, 25 and 30%) of total solids in emulsion and inlet air temperature (160, 170 and 180Â°C) of spray dryer. Response surface methodology was used for analysis of responses (EE, PV and MC) and second order polynomial models were found significantly fitted to the responses with high coefficient of determination. The JSS:SPI ratio of 3.24:1, 23.8% oil loading and 175Â°C dryingair temperature were selected as the optimum conditions after numerical optimization and model validation.